Investigation On Natural Ventilation Provided Through Facades On High Rise Residential Buildings Over Examples - Dikmen, Merve; Limoncu, Sevgul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
Energy crisis in the '70s, have induced awareness on rapidly consume of primary (non -renewable) energy sources and the negative impact of human on environment. Environmental consciousness and conservation of energy has become apparent as an increased awareness in the community. Natural ventilation is a significant factor to save energy by the methods implemented to the buildings according to different environmental factors. The main function of the buildings is fulfilling the requirements of users to live in a healthy artificial environment. Natural ventilation is significant in terms of global economy / energy conservation and users' health, is an important issue that should be taken into consideration in the design stage. Common use of mechanical systems and insulated facades that technology and energy crisis couse, threat to users' health in time. The change of living conditions in consequence of developing technology affected the change of housing units and housing typologies. Many of the naturaly ventilated buildings which are encountered in literature review was found to be office buildings. It is possible to reduce dependence on mechanical systems and ensure user comfort with natural ventilation systems allowing user control in residential buildings, too. Therefore in this study, the necessity of natural ventilation in high rise residential buildigs increasing in today's city and the natural ventilation solutions provided through facades were emphasized. Examples of naturally ventilated high rise residential buildings which have different climate, environmental and building features have been investigated. The inclusion of natural ventilation principles to the structures at the design stage, with an accurate analysis of the climate and environmental data, it is found possible to provide natural ventilation with less energy in many different situations.
Keywords: Multi storey residential buildings; natural ventilation; natural ventilation elements; high rise building; Architecture